Effects of English Medium Instruction (EMI) on students’ academic and speaking performance: comparison between english major and non-english departments - Md. Mahadhi Hasan; Most. Mobina Yesmin; Md. Kamal Hossain (Ilha do Desterro)
The purpose of this paper is to study the effects of the EMI policy on academic improvement and speaking proficiency among the students of private universities in Bangladesh. In addition to the academic implications of EMI, it investigates its impact on English-speaking performance among other related disciplines. A quantitative research methodology was used, with data collected from 120 participants in both English and non-English departments. A survey questionnaire consisting of 45 items was used to collect data on the participants’ perceptions of the effects of EMI on academic and English-speaking performance. Factor analysis and t-test results reveal the pressing nature of the problem given that while students in English departments score high on the impacts EMI has had on undermining academic improvement and language proficiency, those in non-English departments consider EMI facilitative. Overall, the findings presented above might guide further discussions on the EMI policy and give recommendations to both individuals and institutions. As a result, this is a relevant contribution to the language instruction policy in higher education that is mainly concerned with better academic performance and speaking skills acquired by university students in Bangladesh and beyond.